Dynamically modelling and locating solid oxide fuel cells and optimally designing fuzzy stabilisers for multi-machine system. Issue 1 (31st December 2022) - Shahsavari, Hossein; Nateghi, Alireza; Safari, Amin; Azimi Bizaki, Erfan
Abstract : Increasing progress in the field of renewable energy, thanks to the low cost of its resources and increasing public awareness of environmental issues, has led to wide use of these resources in power networks. Among various types of renewable sources, Solid Oxide Fuel Cells (SOFC) have the most potential to connect to the grid as a clean source of electricity according to their attributes. This paper presents a new method for mathematical modelling of multi-machine grids including large-scale SOFC. Since the installation location of SOFC in large-scale networks impacts grid dynamics, it is important to dynamically locate it. This study locates SOFC via the objective function of grid dynamics. Grid connected SOFC generation can effectively and efficiently improve small signal stability. Hence, considering the small disturbance fluctuations and the design of an optimal controller is necessary for the stability of a power system. Consequently, the present study investigates the design of a FLPSO-based power system stabiliser to improve the system's small frequency oscillations. The results of the simulation demonstrate that this controller guarantees the stability of the power system during low frequency disturbances.